2000
DOI: 10.1093/pcp/41.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Intrinsic Annexins Accumulate in Wheat Membranes in Response to Low Temperature

Abstract: Four immunologically related proteins that belong to the annexin family were identified in cold acclimated wheat (Triticum aestivum). Two soluble forms with molecular masses of 34 and 36 kDa were found to bind phospholipid membranes in a calcium-dependent manner. These two forms are similar to the previously reported doublet in several plant species. The other two forms, with molecular masses of 39 and 22.5 kDa, were found associated with the microsomal fraction. Biochemical analysis showed that both forms are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…To circumvent this damage, plant membranes, particularly the plasma membrane, undergo structural changes including the accumulation of mono-or diunsaturated species of phosphatidylcholine which increase cryostability (44,45). Plasma membrane proteins may play an important role during cold acclimation (46)(47)(48). A recent study by Kawamura and Uemura (33) identified substantial changes in the protein content for range of plasma membrane proteins during the early stages of cold acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent this damage, plant membranes, particularly the plasma membrane, undergo structural changes including the accumulation of mono-or diunsaturated species of phosphatidylcholine which increase cryostability (44,45). Plasma membrane proteins may play an important role during cold acclimation (46)(47)(48). A recent study by Kawamura and Uemura (33) identified substantial changes in the protein content for range of plasma membrane proteins during the early stages of cold acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…In its extracellular form, the channel-forming annexin ANXA5 regulates Polycystin-1 (a transient receptor potential channel) at its extracellular N terminus (Markoff et al, 2007), while extracellular ANXA1 causes [Ca 2+ ] cyt increase by activating plasma membrane G-protein-coupled receptors (Babbin et al, 2006). Generally, the known abundance of annexins in the cytosol and their ability to relocate to plasma and endomembranes (Thonat et al, 1997;Breton et al, 2000;Lee et al, 2004;reviewed in Mortimer et al, 2008) place them predominantly as intracellular regulators of [Ca 2+ ] cyt . In this respect, annexins, as regulators of plant channels, can be viewed as being similar to calmodulin.…”
Section: Discussionmentioning
confidence: 99%
“…Maize (Zea mays) annexins have been found to stimulate Ca 2+ -dependent exocytosis in root cap cells (Carroll et al, 1998), the process underlying cell expansion and plant growth (Carroll et al, 1998). Annexin relocation from the cytosol to membranes can occur in response to specific stimuli, such as touch (Thonat et al, 1997), cold (Breton et al, 2000), and salinity , suggesting a role in adaptive signaling. Indeed, Arabidopsis thaliana annexin 1 (ANN1) expression is upregulated by peroxide, salicylic acid (Gidrol et al, 1996), abscisic acid , drought, cold, and salt stress (Cantero et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In wheat, 39 kDa and 25 kDa annexins were induced in response to low temperatures during cold acclimation (Breton et al ., 2000). These results suggest that several types of annexins are temperature-sensitive proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In wheat, novel annexin expressions are induced by low temperatures during cold acclimation (Breton et al ., 2000). These results suggest that the annexin family proteins may be new members of the stress protein family.…”
Section: Introductionmentioning
confidence: 99%